Comparative study of the chemical composition, antioxidant, and antimicrobial activity of the essential oils extracted from Lavandula abrialis and Lavandula stoechas: in vitro and in silico analysis - Radi, Mohamed; Eddardar, Zaina; Drioiche, Aziz; Remok, Firdaous; Hosen, Md. Eram; Zibouh, Khalid; Ed-Damsyry, Brahim; Bouatkiout, Amale; Amine, Sanae; Touijer, Hanane; Salamatullah, Ahmad Mohammad; Bourhia, Mohammed; et al. (Frontiers in Chemistry, 2024)
The objective of this study is to enhance the significance of the Lavandula genus by analyzing the chemical composition, antioxidant properties, and antimicrobial effects of two lavender species found in Oulmès, Morocco: Lavandula abrialis and Lavandula stoechas. The distinctiveness is in the comprehensive methodology that merges in vitro and in silico investigations to evaluate the biological characteristics of the essential oils (EO). This work aims to add value to the Lavandula genus by identifying the chemical composition, antioxidant, and antimicrobial activities of two species lavender from Oulmès in Morocco; Lavandula abrialis and Lavandula stoechas. The uniqueness lies in the integrated approach that combines in vitro and in silico analyses to assess the biological properties of the essential oils (EO). The extraction of essential oils (EO) by hydrodistillation from the aerial parts of Lavandula abrialis gave a high yield of essential oils (2.9%) compared to Lavandula stoechas (2.3%). A GC-MS analysis of the chemical composition revealed 56 chemical compounds, with some variation in the predominant components, representing between 99.98% and 100% of the EOs of the studied lavenders. Their antioxidant activity was assessed using the DPPH test. This method revealed that Lavandula stoechas EO has a higher percentage of free radical inhibition than Lavandula abrialis. The IC50 values demonstrate that the antioxidant activity of ascorbic acid is higher (1.62 g/ml) than the EOs of tested plants. Noteworthy, the EO of Lavandula stoechas is more potent (12.94 g/ml) than that of Lavandula tibialis (34.71 g/ml). Regrading, the antibacterial tests, the EO of Lavandula abrialis was particularly active against Staphylococcus aureus BLACT, which is inhibited at a concentration of 6.25 g/ml, while Lavandula stoechas EO has a strong effect on Escherichia coli, with a MIC of 1.56 g/ml. Concerning the antifungal activity of the EOs, yeasts showed sensitivity toward EOs extracted from both Lavandula tibialis and Lavandula stoechas. Moreover, an in silico study was conducted targeting sarA protein of S. aureus (PDB ID: 2fnp) and NADPH oxidase from L. sanfranciscensis (PDB: 2CDU) and results showed that Ishwarone and Selina-3,7(11)-diene exhibited highest binding energy with -9.8 and -10.8 kcal/mol respectively.